DETECTIVE REALITY AND INDIVIDUAL INTERPRETATION - Alikulovich, Kholikov Bakhodir (OKARA: Jurnal Bahasa dan Sastra, 2016)
The article presents scientific analytical conclusions on the established opinions about literary-theoretical views related to the literary life, psychology of creativity, writerâ€™s skillfulness, spiritual-educational world of a person in fiction as a result of special studies of the close and analogical literary phenomena in fiction writing. Â On the material of the novel â€œGodfatherâ€ by a prominent American writer of the XXth century Mario Puzo and â€œShaytanatâ€ (â€œBand of Devilsâ€) by Uzbek writer Tokhir Malik, the societyâ€™s stability and negative factors influencing social-spiritual life of the society are analyzed.